Oligodeoxynucleotide Containing Disulphide Bond Stabilizes Triplex DNA Structure - Ajay Kumar (E-Journal of Chemistry)
The triplex formation of disulphide containing oligonucleotide with duplex DNA using melting temperature studies is reported. The stability of the triplex formed with disulphide containing oligonucleotide was compared with unmodified oligonucleotide and C-5 propyne deoxyuridine containing oligonucleotide. Melting temperature (Tm) values of the triplexes formed with disulphide containing oligonucleotide were found to be 37 °C and 46 °C at pH 7 and 6 respectively. The triplexes formed with C-5 propyne deoxyuridine substituted oligonucleotide showed Tm values at 27 °C and 42 °C at pH 7 and 6. The Tm values of the triplexes formed with unmodified oligonucleotide were found to be 18 °C and 32 °C at pH 7 and 6 respectively. This clearly demonstrates that disulphide containing oligonucleotide stabilzes triplex DNA structure better than unmodified oligonucleotide as well as C-5 propyne deoxyuridine containing oligonucleotide when targeted with duplex DNA at both the mentioned pH values.